Human Guanylate-Binding Protein 1 Positively Regulates Japanese Encephalitis Virus Replication in an Interferon Gamma Primed Environment - Chhabra, Simran; Sharma, Kiran Bala; Kalia, Manjula (Frontiers in Cellular and Infection Microbiology, 2022)
RNA virus infection triggers interferon (IFN) receptor signaling, leading to the activation of hundreds of interferon-stimulated genes (ISGs). Guanylate-binding proteins (GBPs) belong to one such IFN inducible subfamily of guanosine triphosphatases (GTPases) that have been reported to exert broad anti-microbial activity and regulate host defenses against several intracellular pathogens. Here, we investigated the role of human GBP1 (hGBP1) in Japanese encephalitis virus (JEV) infection of HeLa cells in both an IFNγ unprimed and primed environment. We observed enhanced expression of GBP1 both at transcript and protein levels upon JEV infection, and GBP1 association with the virus replication membranes. Depletion of hGBP1 through siRNA had no effect on JEV replication or virus induced cell death in the IFNγ unprimed environment. IFNγ stimulation provided robust protection against JEV infection. Knockdown of GBP1 in the primed environment upregulated expression and phosphorylation of signal transducer and activator of transcription 1 (STAT1) and significantly reduced JEV replication. Depletion of GBP1 in an IFNγ primed environment also inhibited virus replication in human neuroblastoma SH-SH5Y cells. Our data suggests that in the presence of IFNγ, GBP1 displays a proviral role by inhibiting innate immune responses to JEV infection.